2012
DOI: 10.3109/17549507.2011.604428
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness of Cantonese-speaking pre-school children with cochlear implants

Abstract: The study investigated the phonological awareness abilities of Cantonese-speaking pre-schoolers with cochlear implants. Participants were 15 Cantonese-speaking children with cochlear implants (CIs) aged 3.08-6.10, chronological-age-matched with 15 children with normal hearing. Each participant performed 10 tasks evaluating different levels of phonological awareness abilities and phonological knowledge. The results showed that pre-schoolers with cochlear implants and their normal hearing peers had similar level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The lack of significant difference between the CI and NH groups in phonological detection of syllable-internal units (i.e., rime, onset, and tone) is noteworthy. The findings are partially in agreement with a prior study that revealed equivalent performances between Cantonese-speaking preschool-aged children with CIs and their peers with NH in rime and onset awareness, but not in tone awareness that CI children were outperformed by NH counterparts (Tse & So, 2012). Tse and So (2012) suggested that the compromised tone awareness in implanted children relative to NH controls could be attributable to the impoverished pitch information from CI devices that would contribute to the deficient lexical tone representations for children with CIs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lack of significant difference between the CI and NH groups in phonological detection of syllable-internal units (i.e., rime, onset, and tone) is noteworthy. The findings are partially in agreement with a prior study that revealed equivalent performances between Cantonese-speaking preschool-aged children with CIs and their peers with NH in rime and onset awareness, but not in tone awareness that CI children were outperformed by NH counterparts (Tse & So, 2012). Tse and So (2012) suggested that the compromised tone awareness in implanted children relative to NH controls could be attributable to the impoverished pitch information from CI devices that would contribute to the deficient lexical tone representations for children with CIs.…”
Section: Discussionsupporting
confidence: 91%
“…The findings are partially in agreement with a prior study that revealed equivalent performances between Cantonese-speaking preschool-aged children with CIs and their peers with NH in rime and onset awareness, but not in tone awareness that CI children were outperformed by NH counterparts (Tse & So, 2012). Tse and So (2012) suggested that the compromised tone awareness in implanted children relative to NH controls could be attributable to the impoverished pitch information from CI devices that would contribute to the deficient lexical tone representations for children with CIs. Several plausible reasons are supposed for the inconsistent results in preschool-aged CI users' lexical tone awareness between the prior and the present reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Better PA in Chinese readers has been significantly correlated to better Chinese word recognition (Huang & Hanley, 1995). Within 41 articles comparing children with CIs to their hearing peers, one study (Tse & So, 2012) conducted PA tasks in Cantonese (effect size range from .008 — -.538, see Supplementary Figure A.1) and is unlikely to affect the overall effect size for PA (g = -1.62).…”
Section: Discussionmentioning
confidence: 99%
“…Other phenomenon of interest that may also have an increase in scientific production refers to "Hearing abilities in tonal languages" and "Oral production". The 14 studies on "Hearing abilities in tonal languages" have investigated the variables that affect the auditory skills in cochlear implants users whose language is tonal, such as Mandarin and Cantonese 36,37 . Such surveys are justified by the fact that in tonal languages, the tonal range of speech sets an important dimension to be perceived by the listener (unlike what happens in phonetic languages like English, Portuguese and Spanish) and can transmit different lexical meanings of words 37 .…”
Section: Analysis By Phenomenamentioning
confidence: 99%